2017
DOI: 10.1002/ange.201700341
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Long Oxahelicenes by Polycyclization in a Flow Reactor

Abstract: As eries of oxahelicenes composed of ortho/metaannulated benzene/pyridine and 2H-pyran rings were synthesized on the basis of the cobalt(I)-mediated (or rhodium(I)-or nickel(0)-mediated) double,t riple,o rq uadruple [2+ +2+ +2] cycloisomerization of branched aromatic hexa-, nona-, or dodecaynes,thus allowing the construction of 6, 9, or 12 rings in asingle operation. The use of aflow reactor was found to be beneficial for the multicyclization reactions.T he stereogenic centers present in some of the oligoyness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 51 publications
2
24
0
Order By: Relevance
“…There are only two reports on the single molecule conductance properties of uncharged diazahelicenes, where N ‐heteroatoms served as the anchoring groups . In the first work the theoretical description of mechanical tuning of the single molecule conductance was emphasized, whereas in the second one the single molecule conductance of oxa[9]helicene terminated by pyridine units was reported to be 8.8×10 −4 G / G 0 (log( G / G 0 )=−3.06), which is in reasonable agreement with our measurements assuming that this molecule has n equal to 9 and contains anchoring groups.…”
Section: Resultssupporting
confidence: 87%
“…There are only two reports on the single molecule conductance properties of uncharged diazahelicenes, where N ‐heteroatoms served as the anchoring groups . In the first work the theoretical description of mechanical tuning of the single molecule conductance was emphasized, whereas in the second one the single molecule conductance of oxa[9]helicene terminated by pyridine units was reported to be 8.8×10 −4 G / G 0 (log( G / G 0 )=−3.06), which is in reasonable agreement with our measurements assuming that this molecule has n equal to 9 and contains anchoring groups.…”
Section: Resultssupporting
confidence: 87%
“…Furthermore it has been used to prepare aza[ n ]helicenes such as 2 . Recently the transition‐metal‐mediated [2+2+2]‐cycloisomerization has been utilized for the synthesis of long helicenoids that have regions of linear annulation being part of the helical backbone, as in 3 , or the inclusion of 2H ‐pyranes as in oxa[19]helicenoid ( 4 ) . Using furan formation as the annulating step allows for the convenient preparation of oxa[ n ]helicenes, such as 5 and 6 .…”
Section: Figurementioning
confidence: 99%
“…Removal of the resolving agent, followed by methylation provided the optically pure [13]helicenes ((+)‐ 25 and (−)‐ 25 , ee =99 % for both enantiomers, see the Supporting Information, Figure S1). To the best of our knowledge, these are the longest optically pure helicenes which have synthetically been prepared . Heating (+)‐ 25 at 200 °C in diphenylether for 4 h, no racemization was observed (Supporting Information, Figure S2).…”
Section: Figurementioning
confidence: 99%
“…Along these lines, Chen et al showed that a through-space charge transport can be significantly more efficient in short π-stacked tetraphenylene bridges than through-bond transport over a similar distance, 28 whereas charge transport along the backbone of an oxahelicene comprising 5 conjugated aromatic units was reported to occur efficiently via a through-bond mechanism. 29 Nevertheless, there has been no demonstration of combining multiple conductance pathways in a linear non-conjugated molecule to achieve charge transport over long distances. We now show that this can be achieved using aromatic helical foldamer assemblies.…”
Section: Introductionmentioning
confidence: 99%